Political and ideologicalfoundations of societyasfactors influential onlawmaking (Journal of actual problems of jurisprudence, 2018)
In this article the questions of influence of political and ideological bases are considered on legislative activity of the state. Accordingly a degree and importance of influence of politics of the state open up in the article, other political factors on forming of text of bills and to their process acceptance,and also the role of state ideology is analysed in legislative activity.Key words: law, legislative activity, legislator, political factor, politics, political party, objective factor, human factor, state ideology, legal consciousnesses.